Students’ perspective of a competent medical teacher: A qualitative study - Jayaprakash, R; Sharija, S (Indian Journal of Child Health, 2017)
Background: Current experience shows that at the end of the medical education process, there is relative lack of knowledge, skills, communication, and attitude which are necessary for an effective young doctor. It is the gap in medical teaching. Competency of medical teacher plays an important role in transforming the young medical student into an efficient young doctor to meet this gap. Objectives: To formulate the students’ perspective of a competent medical teacher. Materials and Methods: Qualitative descriptive study was conducted using focus group discussions. The study participants were consented medical students. Results: The transcribed text data were subjected to conventional content analysis and identified 278 meaning units. These codes were categorized and eight themes were generated regarding the students’ perspective of a competent medical teacher. They are good communication skill, adequate knowledge, attitude to demonstrate, concern for students, teaching skill, professional development, personal qualities, and interpersonal skill. Conclusion: The findings of this study can be discussed in teachers training activities under medical education units which may help to bring out attitudinal change and skill development among the medical teachers.